β-Catenin is reduced in membranes of human prolactinoma cells and it is inhibited by temozolomide in prolactin secreting tumor models - Demarchi, Gianina (2023)
INTRODUCTION: Prolactinomas are the most frequent pituitary tumor subtype. Despite most of them respond to medical treatment, a proportion are resistant and become a challenge in clinical management. Wnt/β-Catenin pathway has been implicated in several cancers including pituitary tumors and other sellar region malignancies. Interestingly, Wnt/β-Catenin inhibition augments the cytotoxicity of the chemotherapeutic agent Temozolomide (TMZ) in different cancers. TMZ is now being implemented as rescue therapy for aggressive pituitary adenoma treatment. However, the molecular mechanisms associated with TMZ action in pituitary tumors remain unclear. OBJECTIVES: Our aims in the present study were to evaluate differential β-Catenin expression in human resistant prolactinomas and Wnt/β-Catenin signaling activation and involvement in Prolactin (PRL) secreting experimental models treated with TMZ. RESULTS: We first evaluated by immunohistochemistry β-Catenin localization in human resistant prolactinomas in which we demonstrated reduced membrane β-Catenin in prolactinoma cells compared to normal pituitaries, independently of the Ki-67 proliferation indexes. In turn, in vivo 15 mg/kg of orally administered TMZ markedly reduced PRL production and increased prolactinoma cell apoptosis in mice bearing xenografted prolactinomas. Intratumoral β-Catenin strongly correlated with Prl and Cyclin D1, and importantly, TMZ downregulated both β-Catenin and Cyclin D1, supporting their significance in prolactinoma growth and as candidates of therapeutic targets. When tested in vitro, TMZ directly reduced MMQ cell viability, increased apoptosis and produced G2/M cell cycle arrest. Remarkably, β-Catenin activation and VEGF secretion were inhibited by TMZ in vitro. CONCLUSIONS: We concluded that dopamine resistant prolactinomas undergo a β-Catenin relocalization in relation to normal pituitaries and that TMZ restrains experimental prolactinoma tumorigenicity by reducing PRL production and β-Catenin activation. Together, our findings contribute to the understanding of Wnt/β-Catenin implication in prolactinoma maintenance and TMZ therapy, opening the opportunity of new treatment strategies for aggressive and resistant pituitary tumors.